Alone in the crowd: how adults with learning difficulties cope with social networks problems. - Heyman B; Swain J; Gillman M; Handyside EC; Newman W (Social Science & Medicine)
The relationship between perceived social support and mental health has been the subject of a large quantitative research effort. However, quantification leads to inevitable oversimplification of multidimensional, intersubjective and contextual features of social support. The present paper explores qualitatively the social networks of six adults with learning difficulties (adults), selected from a sample of 32 because of the strategies they used to manage their social worlds. Three adults, who lived with parents, attempted to sustain non-confirmed identities in the face of rejection by others. The other three adults, who were separated from their families, had adopted fatalistic attitudes, despite feeling socially isolated and unsupported. The paper argues that non-confirmed identity maintenance and fatalism are both responses to social contexts that do not support an individual's sense of self-worth. The former is an attempt to manufacture positive identity in the absence of consensual alternatives. The latter involves acceptance of a social world that does not sustain valued social identities. The paper explores in detail the social contexts in which adults attempted to maintain non-confirmed identities or adopted fatalistic attitudes. The research provides a perspective on the management of behaviour defined from a frame of reference external to the individual as 'challenging' or 'problematic'. Carers saw adults who sustained non-confirmed identities as having behaviour problems. However, these problems arose from adults' attempts to maintain self-esteem in stigmatising social contexts. The fatalistic adults did not cause behaviour 'problems' for carers, but only because they had accepted lives which did not give them any sources of positive self-esteem.